ANALISA MODEL KECEPATAN DENGAN PRE STACK DEPTH MIGRATION PADA LAPANGAN ‘X’ - Dimas Sidiq Baskoro; Agus Setyawan; Bambang Mujihardi (Youngster Physics Journal, 2016)
Analysis on Pre - Stack Depth Migration ( PSDM ) has been applied in the data field " X " on line 11 and 48.  Pre - Stack Time Migration ( PSTM ) often get  discontinuity of reflector caused by lateral velocity variations and complex geological structure . It can be overcome by processing the data using an accurate velocity model . Pre- Stack Depth Migration has done by using the velocity model obtained from a tomography velocity models that reflect the actual state of the earth . PSDM able to show better results compared with the results of PSTM , which is able to confirm the continuity of reflectors and more coherent resolution. Keyword:  PSDM, PSTM, lateral velocity variation